2020
DOI: 10.1002/cbf.3581
|View full text |Cite
|
Sign up to set email alerts
|

Cystine‐glutamate antiporter xCT as a therapeutic target for cancer

Abstract: Cystine/glutamic acid reverse transporter (System Xc−), a member of the amino acid transporter family, consists of two subunits, light chain xCT and heavy chain 4F2hc. xCT is the cystine/glutamate antiporter solute carrier family 7 member 11 (SLC7A11), which promotes cystine uptake and glutathione biosynthetic, thus protecting against oxidative stress and ferroptosis. Studies have confirmed that xCT is highly expressed in a variety of tumour and is associated with tumour proliferation, invasion, metastasis, dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 61 publications
0
30
0
Order By: Relevance
“…8 Solute carrier family 7 member 11 (SLC7A11) constitutes the major component of the xCT system and is capable of inhibiting ferroptosis by promoting cystine uptake. 8 Accumulating evidence has shown that SLC7A11 is overexpressed in multiple cancers and can promote tumor progression by retarding ferroptosis, leading to metabolic reprogramming. 9 Therefore, SLC7A11 shows great potential as a new target for cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…8 Solute carrier family 7 member 11 (SLC7A11) constitutes the major component of the xCT system and is capable of inhibiting ferroptosis by promoting cystine uptake. 8 Accumulating evidence has shown that SLC7A11 is overexpressed in multiple cancers and can promote tumor progression by retarding ferroptosis, leading to metabolic reprogramming. 9 Therefore, SLC7A11 shows great potential as a new target for cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…System x c − is a cystine/glutamate antiporter with xCT (Slc7a11) as specific subunit and is located mainly in the central nervous system and peripheral organs related to the immune system. xCT expression is enhanced in conditions of increased oxidative stress and/or inflammation, and inhibition of system x c − has been proposed as a treatment strategy for several neurological disorders as well as for diverse cancer types ( Lewerenz et al, 2013 ; Massie et al, 2015 ; Koppula et al, 2018 ; Liu et al, 2020 ). However, despite many attempts, till now none of the available inhibitors are selectively targeting system x c − .…”
Section: Introductionmentioning
confidence: 99%
“…Besides the enzymes that control the glutamine metabolism directly, a cystine/glutamate exchange transporter called system X also plays a critical role in intracellular GSH biosynthesis [ 84 ]. The expression of the light chain of system X is promoted by Nrf2 under the stimulation of oxidative stress, which is closely related to radio- and chemoresistance in tumour cells [ 85 , 86 ]. In Nrf2 knockdown cells, glutathione metabolism is affected [ 80 ], showing the pivotal role of Nrf2 in glutathione metabolism.…”
Section: Antioxidative Stress-related Pathways That Lead To Therapmentioning
confidence: 99%